2019
DOI: 10.4253/wjge.v11.i2.103
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided drainage of the biliary system: Techniques, indications and future perspectives

Abstract: Over the last decade, endoscopic ultrasound-guided biliary drainage (EUS-BD) has evolved into a widely accepted alternative to the percutaneous approach in cases of biliary obstruction with failed endoscopic retrograde cholangiopancreaticography (ERCP). The available evidence suggests that, in experienced hands, EUS-BD might even replace ERCP as the first-line procedure in specific situations such as malignant distal bile duct obstruction. The aim of this review is to summarize the available data on EUS-BD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 68 publications
(77 reference statements)
0
26
0
4
Order By: Relevance
“…The current recommended technique by most authors includes 19G needle puncture of the extrahepatic bile duct from the duodenal bulb or second duodenal portion, with the endoscope in the short position, and passage of a 0.025-inch guidewire. [ 24 ]…”
Section: Eus and Endoscopic Retrograde Cholangiopancreatography Collamentioning
confidence: 99%
“…The current recommended technique by most authors includes 19G needle puncture of the extrahepatic bile duct from the duodenal bulb or second duodenal portion, with the endoscope in the short position, and passage of a 0.025-inch guidewire. [ 24 ]…”
Section: Eus and Endoscopic Retrograde Cholangiopancreatography Collamentioning
confidence: 99%
“…There are different approaches for EUS-BD, indication for which depends on the etiology (malignant or benign), location (distal or proximal) of the biliary obstruction and the upper gastrointestinal tract anatomy (surgically altered or not). Prerequisite for endoscopic EUS-BD is the visualization of the dilated extra—and/or intrahepatic bile ducts, respectively, followed by the puncture of the target duct with a needle or a dedicated access device (i.e., LAMS) [ 33 ]. Access to the left intrahepatic bile ducts is usually attempted from the oral part of the stomach whereas the optimal position to sight out the CBD is the apical duodenum.…”
Section: Clinical Application and Performance Of Eus In Biliary DImentioning
confidence: 99%
“…However, the rendezvous maneuver can fail because of an inaccessible papilla (altered anatomy, duodenal obstruction, gastric outlet syndrome or the presence of enteral stents) or a failure to advance the wire through a stricture. In these patients, HG or CD are feasible drainage techniques 132. Four meta-analyses reported that EUS-BD was clinically successful in 87–94% of cases with adverse events reported in 16–29% 133,134.…”
Section: Endoscopic Managementmentioning
confidence: 99%